2016
DOI: 10.1039/c6sc02520j
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-defined oligo(ortho-arylene) foldamers derived from the benzannulation of ortho(arylene ethynylene)s

Abstract: A Cu-catalyzed benzannulation reaction transforms ortho(arylene ethynylene) oligomers into ortho-arylenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 43 publications
(21 reference statements)
0
30
0
Order By: Relevance
“…27,49 This model is admittedly simplied: it fails, for example, to account for steric effects of substituents, and the twisting of the backbone in longer oligomers can certainly lead to additional conformational stabilization via other interactions beyond arene-arene stacking (e.g., edge-to-face arene-arene interactions). 33 However, it provides a very useful framework within which to understand o-phenylene folding, and can be rened by using DFT calculations to more-accurately predict conformer energies. 49 An o-phenylene hexamer can therefore adopt ve unique conformations in the A/B pool (and their enantiomers in the A 0 / B 0 pool), shown in Fig.…”
Section: Synthesis Of Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,49 This model is admittedly simplied: it fails, for example, to account for steric effects of substituents, and the twisting of the backbone in longer oligomers can certainly lead to additional conformational stabilization via other interactions beyond arene-arene stacking (e.g., edge-to-face arene-arene interactions). 33 However, it provides a very useful framework within which to understand o-phenylene folding, and can be rened by using DFT calculations to more-accurately predict conformer energies. 49 An o-phenylene hexamer can therefore adopt ve unique conformations in the A/B pool (and their enantiomers in the A 0 / B 0 pool), shown in Fig.…”
Section: Synthesis Of Componentsmentioning
confidence: 99%
“…23,24 Our work has focused on the o-phenylenes, simple polyphenylenes 25 that adopt helical conformations in solution driven by (offset) arene-arene stacking interactions parallel to the helical axis. [26][27][28][29][30][31][32][33][34] In previous work on o-phenylene-based macrocycles, we showed that amino-functionalized o-phenylene tetramers could be co-assembled with a series of rodshaped dialdehyde linkers, giving, for example, the [3 + 3] macrocycles oP 4 (Phen) 3+3 and oP 4 (DPB) 3+3 shown in Chart 1 (i.e., 3 o-phenylenes + 3 linkers). 35 The resulting twisted macrocycles [36][37][38][39][40] are shape-persistent but have well-dened degrees of conformational freedom via the foldamer moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Kurzaufsätze performed on aconjugated polymer backbone.T his method, in combination with the Scholl reaction, proves to be very efficient to prepare PA Hs [70] and GNR. [71] When polymer 15 b was used as the precursor,abenzannulation-Scholl sequence gave [13] A GNR 16 b (3p + 1f amily) that showed ambipolar transport properties in FETs. [72] Them ain limitation for the use of such wide GNR is the very low solubility in common organic solvents,m aking the solution processing rather difficult.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…These artificial foldamers can not only serve as protein–protein interaction mediators and molecular receptors like biopolymers, but also exhibit great potential in molecular materials, such as molecular containers and tubes, sensors, molecular shuttles and machines, and so on. However, although numerous artificial foldamers have been reported, with confines ranging from flexible to rigid, folded types forming a secondary folded motif are still comparatively rare . While most foldamers adopt a secondary structure in helices, other types of folding, such as parallel folding of the chemical units, are very rare .…”
Section: Introductionmentioning
confidence: 99%